(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the activities of American artists who mobilized, in 2002, against the prospect of American intervention in Iraq, and then against the war itself1. Analyzing these protests of artists and entertainment professionals means in reality to be interested in multiple and diverse occupational groups and social games. The individuals mobilized and gathered, whether by journalists, political actors, or the organizations to which they belong, under the unified name of "anti-war artists", thus exercise heterogeneous professions: painters, sculptors, draftsmen and Caricaturists, musicians and performers, actors and directors are agglomerated under this label. In fact, in spite of what separates them, they are bound by interdependent relations in the mobilization against the war which they participate to build and for which they cooperate sometimes directly.